PEMBERDAYAAN MASYARKAT MELALUI PENYULUHAN KESEHATANDEMAM BERDARAH DENGUE PADA MASYARAKAT DI DUSUNKEDUNGJAGO DESA KEDUNGREJO KECAMATANPURWODADI KABUPATEN GROBOGAN - Wahyu Riniasih; Rini Sri Purwati; Bagus Indra Pamungkas; Desyika mayasari; Evi Puspitasari; Farhan Muhammad Najib (LPPM AN Nuur, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus which is spread through the bite of the Aedes mosquito, especially the Aedesa egypti, which is the fastest growing mosquito throughout the world. Transmission of this virus is more likely to occur in countries with tropical and subtropical climates. This is associated with increasing temperatures, and changes in the rainy and dry seasons are considered factors that increase the risk of dengue virus transmission (Slani et al., 2024). Metodology : carry out nonphysical intervention programs such as health education about Dengue Hemorrhagic Fever (DHF). This activity consists of 3 stages, namely planning, preparation and implementation. In the planning stage, students coordinate with the hamlet head, village midwife, RT head, for observations and discussions regarding Dengue Hemorrhagic Fever (DBD) education..Results: The results of implementing activities in health education about dengue hemorrhagic fever (DHF) can be seen after the health education by asking respondents to explain again what has been explained, with the results of respondents experiencing an increase in the sufficient knowledge category, namely 18 respondents (93.3%) and experiencing a decrease in the category Lack of knowledge, namely 2 respondents (6.7%). output achieved. Conclusion: Through the implementation of the activity